Microactuators and micromechanisms proceedings of MAMM 2014, Timisoara, Romania, October 2-4, 2014 - MAMM (Workshop) Timisoara, Romania) 2014; Lovasz, Erwin-Christian; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book contains applications of micromechanisms and microactuators in several very modern technical fields such mechatronics, biomechanics, machines, micromachines, robotics and apparatuses. It includes the accepted reviewed papers of researchers specialized in the topics of the conference: microactuators and micro-assembly, micro sensors involving movable solids, micro-opto-mechanical devices, mechanical tools for cell and tissue studies, micromanipulation and micro-stages, micro-scale flight and swimming, micro-robotics and surgical tools, micron-scale power generation, miniature manufacturing machines, micromechatronics and micro-mechanisms, biomechanics micro and nano scales and control issues in microsystems. The presented applications of micromechanisms and microactuators in many technical fields will interest industrial companies and encourage scientifical knowledge and cooperation between academia and industry.
Electronic reproduction.
Keywords: Microactuators -- Congresses; Microelectromechanical systems -- Congresses; Electronic books